2015
DOI: 10.3892/br.2015.543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2,4,6-trimethyl-N-[3-(trifluoromethyl)phenyl]benzene-sulfonamide on calcium influx in three contraction models

Abstract: 2,4,6-Trimethyl--[3-(trifluoromethyl)phenyl]benzenesulfonamide (m-3M3FBS) activates phospholipase C and stimulates apoptosis; however, in smooth muscle cells it may increase the perfusion pressure. The main aim of the present study was to evaluate the physiological effect of direct stimulation of phospholipase C on vascular smooth muscle reactivity using three contraction models. Experiments were performed on the isolated and perfused tail artery of Wistar rats. The contraction force in the present model was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…m-3M3FBS is responsible for the increase in calcium influx from intra-and extracellular calcium stores that activate G-protein-coupled receptors, including α 1 -adrenoceptors and vasopressin receptors, thus stimulating vascular smooth muscle cells. In a previous study by our group, the same increase was found during extra-receptor stimulation, such as during direct stimulation of G-protein with mastoparan-7; however, the presence of m-3M3FBS did not modify the arterial muscle reactivity following direct stimulation of L-type calcium channels with the calcium agonist Bay K8644 (13).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…m-3M3FBS is responsible for the increase in calcium influx from intra-and extracellular calcium stores that activate G-protein-coupled receptors, including α 1 -adrenoceptors and vasopressin receptors, thus stimulating vascular smooth muscle cells. In a previous study by our group, the same increase was found during extra-receptor stimulation, such as during direct stimulation of G-protein with mastoparan-7; however, the presence of m-3M3FBS did not modify the arterial muscle reactivity following direct stimulation of L-type calcium channels with the calcium agonist Bay K8644 (13).…”
Section: Introductionmentioning
confidence: 88%
“…Activation of PLC is a key event in numerous metabotropic receptors, the physiological response of which was assessed in the present study. Inhibition of PLC function leads to a reduction in the calcium ion concentration in the cytoplasm of cells activated by the stimulation of α1-adrenergic receptors (13,18,19), endothelin receptor type A (20) and angiotensin II receptor type-1 (21). Furthermore, it has been demonstrated that the increase in cytoplasmic calcium concentration induced by PLC is significant at the molecular level and able to induce a significant physiological reponse (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximal response of tissue (E max ) was calculated as a percent of the maximal response for PHE. Half maximal effective concentration (EC 50 ) was estimated using classical pharmacologic methods with pD2 as the negative logarithm of the EC 50 , similarly to previous studies (30). The number of CRCs and E max were used in all calculations estimating the statistical significance.…”
Section: Drugs and Solutionsmentioning
confidence: 99%